Correlates of hypertension among urban Asian Indian adolescents. Issue 12 (12th August 2010) - Goel, Ruchika; Misra, Anoop; Agarwal, Sunil K; Vikram, Naval
Abstract : Objective: Primary hypertension has become increasingly common in children but remains largely understudied, underdiagnosed and undertreated. This study examines the relationship between hypertension in adolescents and various markers of obesity, serum lipid levels, fasting blood glucose (FBG), haemoglobin A1c (HbA1c) and family history of hypertension. Design/settings: A cross-sectional population-based study of 1022 students aged 14–19 years in New Delhi, India. Main outcome/exposures: Those with age, gender and height specific blood pressure >95th percentile (derived from study data) or >130/85 mm Hg were considered hypertensive. Various markers of obesity, FBG, HbA1c and serum lipid levels were divided into quartiles and the odds ratios of hypertension calculated for the highest quartiles with reference to the lowest. Results: Hypertension was seen in 65 (6.4%) adolescents (2.7% isolated systolic, 2.0% isolated diastolic and 1.7% both). The odds of having hypertension were higher for those in the highest versus lowest quartiles of various measures of obesity such as body mass index (OR 2.90; 95% CI 1.40 to 6.12) and waist circumference (OR 5.21; 95% CI 2.14 to 12.17). A parental history of hypertension was associated with diastolic hypertension in the child (OR 2.21; 95% CI 1.13 to 4.33); the odds ratio decreased after simultaneous adjustment for salt intake (OR 1.98; 95% CI 1.00 to 3.94). In a multivariable model with backward elimination, waist circumference and triglycerides were the strongest predictors of hypertension, further suggesting that the relationship is stronger with central than peripheral obesity. Conclusion: Hypertension in Asian Indian adolescents is associated with obesity, higher serum lipids and a family history of hypertension.